Shark week. Disc two. [videorecording (DVD)] : 20th anniversary collection (Image Entertainment, 2007)
Explore the science, myths and mystery of this fearsome predator in favorite Discovery Channel programs from Shark Week-- the series that has been exciting fans for 20 years.